Islamic Education Value in the Bemeteng Tradition of Malay Semanga Village' Sambas Regency - Ma'ruf Ma'ruf; Juliansyah Juliansyah; Jumadir Jumadir (AT-TURATS, 2021)
Bemeteng tradition for  the people  of Melayu Semanga Village' is a tradition of meetings to facilitate the preparation of the wedding reception held three or four days before the wedding reception is held. The  Malay community of  SemangaVillage'  Sambas Regency still maintains the tradition of bemeteng as a form of gotong royong to help others in their community life. Gotong royong itself is one of the noble values of the Indonesian nation that needs to be maintained and preserved. This research aims to find out  how the implementation of bemeteng  traditions  and  Islamic educational values in the bemeteng tradition in the Malay community of  Semanga' Sambas Regency. This article is a case study study using a qualitative approach, with data collection using interview techniques,  participant  observation andumentationdocks,  with  miles and huberman model analysis, including: data reduction, data presentation, conclusion withdrawal and verification.   The results showed that the values of Islamic education in this bemeteng tradition are as follows:  First,the value of silaturahim; Second,the value of deliberation; Third,the value of alms; Fourth,the value of caring; Fifth,the value of gotong-royong; Sixth,The value glorifies; and  seventh,the value of the degreeequation. Of course, these values become guidelines in a society that remains alive and becomes a tradition to this day.